Potential of development of economic cooperation between Russia and EAEU and CIS countries - A. A. Migranyan (Проблемы постсоветского пространства)
The article examines the peculiarities of the economic situation and the potential for the development of regional integration of Russia and the CIS and EAEU countries. The complexity of the current economic downturn against the backdrop of the COVID-19 pandemic and the turbulence of world energy markets has a mixed impact not only on the economic downturn in the countries of the region, but also on integration processes, their nature and development prospects. In this context, the study of a set of interrelated processes from the point of view of the formation of economic policies of countries, their foreign economic guidelines and goals is relevant. At the same time, the methodology for integrated assessment of the development potential of regional integration is based on the following assumptions: the need to coordinate and develop economic development strategies and geopolitical strategies; creating the attractiveness of the Russian economy as a core of integration; development of common energy markets as the basic platform for integration in the EAEU.